2006
DOI: 10.1186/1471-2407-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible transcription factor-1α promotes hypoxia-induced A549 apoptosis via a mechanism that involves the glycolysis pathway

Abstract: Background: Hypoxia-inducible transcription factor-1α (HIF-1α), which plays an important role in controlling the hypoxia-induced glycolysis pathway, is a "master" gene in the tissue hypoxia response during tumor development. However, its role in the apoptosis of non-small cell lung cancer remains unknown. Here, we have studied the effects of HIF-1α on apoptosis by modulating HIF-1α gene expression in A549 cells through both siRNA knock-down and over-expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 18 publications
(25 reference statements)
7
52
0
Order By: Relevance
“…In a second hypothesis, HIF may play a role through the upregulation of glycolytic pathway. In A549 cells, knocking down HIF-1␣ inhibited glycolysis, increased the pH of the culture medium, and protected the cells from hypoxia-induced apoptosis (30). These studies suggest a primordial role of HIF in hypoxia-induced apoptosis and underscore the possibility that HIF acts through several pathways.…”
Section: Effect Of Hypoxia On Proteins Involved In Glucose Metabolismmentioning
confidence: 73%
See 2 more Smart Citations
“…In a second hypothesis, HIF may play a role through the upregulation of glycolytic pathway. In A549 cells, knocking down HIF-1␣ inhibited glycolysis, increased the pH of the culture medium, and protected the cells from hypoxia-induced apoptosis (30). These studies suggest a primordial role of HIF in hypoxia-induced apoptosis and underscore the possibility that HIF acts through several pathways.…”
Section: Effect Of Hypoxia On Proteins Involved In Glucose Metabolismmentioning
confidence: 73%
“…HK-I is the predominant isoform in human alveolar epithelial cells A549 under normoxic conditions. However, the hypoxic regulation of HK-I remains under debate since Riddle and coworkers (44) reported that this isoform was not regulated by hypoxia, whereas a recent paper by Luo et al (30) showed that similar experimental hypoxic conditions increased HK-I mRNA levels. HK-II is less expressed in normoxia, but its mRNA expression as well as protein expression and enzymatic activity are dramatically induced by hypoxia (44).…”
Section: Effect Of Hypoxia On Proteins Involved In Glucose Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…The role of p300 in ESC metabolism remains elusive. By monitoring glucose consumption and extracellular lactate production, we found that undifferentiated Cited2 ⌬/Ϫ ESCs metabolize ϳ20% more glucose via aerobic glycolysis than WT counterparts, with a concomitant regulation of glycolysis-associated genes, such as HK1 and PFK1-L. HK1 is a target gene of Oct4 and HIF-1 (41,50), two transcription factors previously shown to be modulated by Cited2 (8,22). A ChIP assay indicated that Cited2 is recruited to the HK1 gene promoter, further supporting the direct role of Cited2 in coordinating HK1 expression and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells can also lower their level of energy production, and if so, glucose consumption and acidosis will not change rapidly. Indeed, HIF-1 not only stimulates glycolysis [71], it also suppresses mitochondrial function and oxygen consumption by directly transactivating the gene encoding pyruvate dehydrogenase kinase (PDK-1). PDK-1 inactivates pyruvate dehydrogenase, an enzyme of the Krebs cycle [72,73].…”
Section: Hypoxia and Acidosismentioning
confidence: 99%